Evaluasi Kesesuaian Standar Sni 6728 1:2015 Untuk Kebutuhan Air Bersih Rumah Tangga: Studi Kasus Pulau Gili Iyang - Nathanael, Rinaldy Jose; Mahardhika, Deedhat Nugraha; Heta, Muhammad Falih Ramadhan; Febrina1, Alvina Iedha; Isnadina, Dwi Ratri Mitha (Syntax Literate, 2025)
Household drinking water needs are often estimated solely based on population size, without adequately considering local characteristics. This study aims to assess household drinking water requirements in a semi-urban island setting, using Gili Iyang Island in Sumenep Regency as a case study. The analysis refers to the Indonesian National Standard (SNI) 6728-1:2015, which defines the daily water requirement for semi-urban areas as 60–90 liters per person. Data were collected through a questionnaire survey involving 100 respondents and analyzed quantitatively using Microsoft Excel and the Kruskal–Wallis statistical test via SPSS. The results indicate that the average household water consumption in Gili Iyang is 132.20 liters per person per day, significantly exceeding the SNI range. Economic status was found to have a statistically significant influence on water consumption levels (p = 0.001), while educational level did not show a significant effect (p = 0.137). These findings suggest that determining household drinking water needs should not rely solely on regional classification and population figures but must also account for local socio-economic factors. Therefore, this study serves as a basis for water supply system development in Gili Iyang Island and offers valuable insights for evaluating and planning future water supply systems, particularly for island regions with similar conditions.